Nível de atividade física no lazer, características sociodemográficas e doenças crônico-degenerativas em pessoas idosas brasileiras: pesquisa nacional de saúde, 2019 - Freitas, Ana Michele Saragozo de (2024)
Introduction: Health interventions for elderly people must consider the association between physical activity, sociodemographic factors and chronic noncommunicable diseases. Objective: To verify the association between leisuretime physical activity, sociodemographic factors and Chronic Noncommunicable Diseases (NCDs) in Brazilian elderly people. Methods: In accordance with the standards of the Postgraduate Program in Physical Education/UFS, the “B” model of dissertation was chosen, including two studies (study 1 and study 2) previously submitted and approved in indexed and reference journals in the area. Both studies are descriptive, with a cross-sectional design, carried out using secondary data from the 2019 National Health Survey – Brazil, with a total sample of 91,683 individuals of great national representation and a data analysis carried out using Quantilic Regression. Results: Study 1: This study aimed to verify the association between leisure-time physical activity, sociodemographic factors and chronic degenerative diseases. It was found that elderly people aged between 60 and 79 years old up to quantile 50, had a higher level of leisure-time physical activity and females presented lower values in all quantiles, especially from quantile 50. The subjects who self-declared “whites” showed significant differences up to quantile 50. Subjects who lived in rural areas presented lower values than those living in urban areas in all quantiles, especially from the median. Considering health conditions, it was found that subjects who did not report any chronic illness had better levels of leisure-time physical activity, especially from the 75th quantile onwards. Study 2: The objective was to verify the association between sociodemographic variables and NCDs in relation to the level of leisure-time physical activity in long-lived elderly people in Brazil. Where he showed that individuals aged between 80 and 90 years old, male, declared to be of white race/ethnicity, with some level of education, who lived in urban areas, with greater emphasis on the north and southeast regions, are more active in leisure. In relation to NCDs, those who reported not having any type of NCD are more active than long-lived people who report having an illness. Of those who stated that they had a NCD, “high blood pressure” was considered to be more active compared to those who reported having “diabetes mellitus” and “heart disease”. Conclusion: There is a direct relationship between the time spent on leisure-time physical activity, sociodemographic variables, NCDs and the different Brazilian regions. In which the strategies and actions focus their activities on the inequalities that exist in the age group itself, as well as in the different Brazilian regions, with specifications for each population group, seeking to increase the practice of physical activity during leisure time.